Absorptive capacity and post-acquisition inventor productivity - Katrin Hussinger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Inventors often experience a low productivity after their company has been subject to a merger or acquisition (M&As). It is of central managerial interest to identify factors facilitating the integration of new inventive staff and thereby counteracting innovation declines after M&As. This paper provides empirical evidence into the role of acquiring firms' absorptive capacity for the post-merger patent productivity of the acquired inventors. Based on a sample of 544 inventors employed by European acquisition targets in the period 2000-2001 it is shown that the post-merger productivity of acquired inventors is significantly higher within acquiring firms with a distinct absorptive capacity. It can be concluded that absorptive capacity is a firm capability that enhances the integration of inventors after firm takeovers.
Keywords: O30; O32; G34; 330; M&As; absorptive capacity; inventor productivity; Übernahme; Erfindung; Produktivität; Innovationsmanagement; Wissenstransfer; Schätzung; Deutschland